Penerapan Algoritma Random Walk Untuk Procedural Map Pada Game “The Last Hope” 2D - Muhammad Ijai; Arbansyah, Arbansyah; Suryawan, Sayekhti Harits (Computer Science and Information Technology, 2023)
Games are activities that aim to provide fun and offer certain rules and challenges, with the aim of creating a dynamic and interesting gaming experience. This research aims to overcome the problem of repetition in making maps in the game "The Last Hope" by applying the Random Walk technique to create maps procedurally. In this research, the Random Walk algorithm was implemented using the C# programming language and created using Unity 2D. The research results show that the use of the Random Walk technique is successful in creating dynamic map variations in each game session, overcoming repetition which causes boredom for players. The implication of this research is increased game replayability, allowing players to enjoy a more interesting and dynamic gaming experience because they will not face the same map every time they start the game. Thus, the use of the Random Walk Algorithm to create procedural maps can make a significant contribution to improving the playing experience of the game "The Last Hope" and similar games in the Roguelike genre.